2019
DOI: 10.1164/rccm.201810-1976oc
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variations in Ambient Ultrafine Particles and the Incidence of Childhood Asthma

Abstract: Word count: 3490At a Glance Commentary: Scientific Knowledge on the Subject: Ambient fine particulate matter (PM2.5) exposure in utero has been associated with the development of childhood asthma. However, little is known regarding the impact of ambient ultrafine particles (<0.1 μm) (UFPs) on childhood asthma development What this Study Adds to the Field: Our findings suggest that UFPs exposure during the second trimester of pregnancy was associated with an increased risk of developing asthma in children befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 54 publications
5
46
0
Order By: Relevance
“…It is well established that air pollution contributes to worsening asthma control and increases the risk of asthma exacerbations. Furthermore, perinatal exposure to ambient ultrafine particles (<0.1 mm diameter) and maternal exposure to traffic‐related NO 2 during pregnancy have been linked to the onset of asthma in children 18,19 . It is of note that we observed differences in allergic diseases between rural children using wells or mains water supply, with a dose‐response relationship between bacterial content in drinking water and the risk of allergies.…”
Section: Discussionsupporting
confidence: 68%
“…It is well established that air pollution contributes to worsening asthma control and increases the risk of asthma exacerbations. Furthermore, perinatal exposure to ambient ultrafine particles (<0.1 mm diameter) and maternal exposure to traffic‐related NO 2 during pregnancy have been linked to the onset of asthma in children 18,19 . It is of note that we observed differences in allergic diseases between rural children using wells or mains water supply, with a dose‐response relationship between bacterial content in drinking water and the risk of allergies.…”
Section: Discussionsupporting
confidence: 68%
“…Some epidemiological studies have found associations between ultrafine particle exposure and respiratory effects such as asthma, inflammation processes in children, changes in children's blood pressure, and even alterations in cognitive development . In the same way, higher doses of UFP, as a consequence of an elevated environmental UFP concentration, have been correlated to larger lifetime cancer risks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the alveolar region shows the highest percentage of deposition of UFP from these devices, the majority of the particles deposited being smaller than 100 nm. 81 Some epidemiological studies have found associations between ultrafine particle exposure and respiratory effects such as asthma, 82 inflammation processes in children, 16 changes in children's blood pressure, 17 and even alterations in cognitive development. 18 In the studies reviewed here, mean UFP levels in children-specific microenvironments were variable and oscillated between 0.1·10 4 and 14.0·10 4 part/cm 3 .…”
Section: Patterns Of Ufp Levels In Microenvironments and Personal Ementioning
confidence: 99%
“…Another important risk in the incidence of pediatric asthma is the composition of PM. Authors have suggested that perinatal exposure to UFPs during a critical period of lung development was linked to the onset of asthma in children, independent of PM 2.5 and NO 2 [20]. However, an investigation from Taiwan determined that particulate matter ≤ 2:5 μm (PM 2.5 ), particulate matter ≤ 10 μm (PM 10 ), sulfur dioxide (SO 2 ), and nitrogen dioxide (NO 2 ) were positively associated with childhood asthma hospitalization rate, while ozone (O 3 ) was negatively associated with childhood asthma hospitalization rate.…”
Section: The Impact Of Pm On Asthma In Childrenmentioning
confidence: 99%